Chemopreventive Efficacy of Andrographis paniculata on Azoxymethane-Induced Aberrant Colon Crypt Foci In Vivo - Al-Henhena, N.; Ying, R.P.Y.; Ismail, S.; Najm, W.; Khalifa, S.A.M.; El-Seedi, H.; Abdulla, M.A. (Public Library of Science, 2014)
Andrographis paniculata is a grass-shaped medicinal herb, traditionally used in Southeast Asia. The aim of this study was to evaluate the chemoprotective effects of A. paniculata on colorectal cancer. A. paniculata ethanol extract was tested on azoxymethane (AOM)-induced aberrant crypt foci (ACF) in vivo and in vitro. A. paniculata treated groups showed a significant reduction in the number of ACF of the treated rats. Microscopically, ACF showed remarkably elongated and stratified cells, and depletion of the submucosal glands of AOM group compared to the treated groups. Histologically, staining showed slightly elevated masses above the surrounding mucosa with oval or slit-like orifices. Immunohistochemically, expression of proliferating cell nuclear antigen (PCNA) and β-catenin protein were down-regulated in the A. paniculata treated groups compared to the AOM group. When colon tissue was homogenized, malondialdehyde (MDA) and nitric oxide (NO) levels were significantly decreased, whereas superoxide dismutase (SOD) activity was increased in the treated groups compared to the AOM group. A. paniculata ethanol extract showed antioxidant and free radical scavenging activity, as elucidated by the measure of oxidative stress markers. Further, the active fractions were assessed against cell lines of CCD841 and HT29 colon cancer cells.